Sign at Fort Buford Historic Site, North Dakota - Kempenich, Mark, 1907-1972 (North Dakota State University Libraries, Institute for Regional Studies, 1971)
View showing wooden sign supported by field stone pillars. Text on the sign states, “Fort Buford Historic Site. Fort Buford, A United States military post named in honor of General John Buford of Gettysburg fame, was established on this location in the fall of 1866. Preceding it on this site were two trading posts, Fort William erected in 1833 and Fort Mortimer built in 1843. Being of strategic importance at the focal point of steamboat traffic to the west, Fort Buford played an important and colorful part in opening the frontier for permanent settlement. Famous Indian prisoners at the fort included Chief Joseph, Crow King, Rain-In-The Face, Gall, and Sitting Bull. Sitting Bull with about 200 stragglers, the last of the hostile Sioux, surrendered here in 1881. In 1895 the fort was dismantled and the garrison was transferred to Fort Assiniboine, Montana. The original adobe buildings providing quarters for 300 men were later replaced by about 100 frame buildings. Though most of the building were sold and removed upon dismantling the fort, a stone powder magazine and the headquarter building are preserved on their original sites. The old military cemetery is also preserved.” Over the sign is a silhouette of an Indian seated on horseback. Slides; Color images; 5 x 5 cm. Title supplied by staff.